Investigation on shrinkage behaviour of kaolin clay - Chegenizadeh, Amin; Nikraz, Hamid (Kasetsart University, Thailand, 2012)
As evaporation prevails, soils lose water and shrink upon desiccation, which lead to formation of desiccation cracks. The cracking of desiccated clay soils is problematic to many civil structures hence an adequate understanding of the desiccation cracking process is of great significance. To build this understanding, knowledge of how crack forms, their position, orientation and connectivity in space are necessary. This paper aims to investigate shrinkage problem deeply. A series of shrinkage test were conducted. The container dimensions were 50mm X50mm X 50mm. the soil was selected as kaolin clay. Different initial moisture content of 45% and 40% considered. The results proved that water content decreased as desiccation rate increased. The engineering graph of change in water content versus time and shrinkage strain versus change in water content was plotted for each test. The desiccation curves shows similar behaviour for different initial moisture content as finally reached the balance with local climate.